Efisiensi Produksi Briket Batok Kelapa untuk Ekonomi Sirkular - Grace Evelyn; Anas Miftah Fauzi; Moh. Yani (Jurnal Penelitian Pendidikan IPA, 2026)
Indonesia through its Enhanced Nationally Determined Contribution (ENDC), targets a 31.89% reduction in greenhouse gas (GHG) emissions with national efforts and 43.20% with international assistance by 2030. The purpose of this study is to develop quality control of materials and evaluate the optimation of using carbon waste in coconut charcoal briquette production. The laboratory test method by CHNS provides the quantitative data of carbon emission high risk in coconut shell charcoal raw, semi-finished materials, and finished briquette. The method of analytical hierarchy process (AHP) is used to find that penta-helix collaboration scheme between between government, industries, institutions, societies, and consumers has the AHP highest priority with score 0.71. The combination of reutilizing energy based on a reject briquette oven has been proven to reduce emissions into make carbon neutral. Export-standard shisha briquettes based on CHNS has the highest carbon concentration (77.57%) and the second highest is oven fuel powder/reject briquette material (59.87%), means the briquettes have a maximum combustion rate and minimal ash release into the air. This work builds a regulation concept of agro-industry sector in the practice of material quality control for clean, low-carbon production.